Return of the QA: A Comparative Analysis of Competencies and Skills for Quality Analysts in Brazil (2021–2025) - Arruda, João Pedro Souza; Yabe, Daniela Godinho; Souza, Alinne Cristiane Corrêa; Souza, Francisco Carlos M.; Souza, Cleidson R. B. de; Pinto, Victor Hugo Santiago C. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de Software, 2025)
Background: The software industry has undergone rapid changes driven by agile methodologies, continuous delivery pipelines, and increased automation. As system complexity and quality demands grow, the role of Quality Analysts (QAs) has become increasingly critical. This shift is particularly relevant in the current context, characterized by the rapid evolution of QA practices, technological advancements, and the increasing adoption of AI-based tools that provide assisted support throughout the software development process. Objectives: This study aims to identify the key technical and behavioral competencies that characterize high-performing QAs, from the perspective of experienced practitioners in the Brazilian software industry. Method:We carried out two large-scale surveys involving Brazilian companies, conducted in 2021 and 2025, with a total of 169 participants. Results: The findings reveal a strong and growing demand for soft skills, especially communication and critical thinking, alongside solid technical foundations. Respondents emphasized the evolving and multidisciplinary nature of the QA role in modern software development contexts. Conclusions: This research offers a comprehensive and recent overview of industry expectations regarding QA analyst competencies in Brazil. The results provide actionable insights for those seeking to advance in the QA field, educators aiming to align curricula with market demands, and organizations aiming to strengthen their software quality assurance capabilities.